2009
DOI: 10.1093/jxb/ern355
|View full text |Cite
|
Sign up to set email alerts
|

Male gametophyte development: a molecular perspective

Abstract: Pollen grains represent the highly reduced haploid male gametophyte generation in flowering plants, consisting of just two or three cells when released from the anthers. Their role is to deliver twin sperm cells to the embryo sac to undergo fusion with the egg and central cell. This double fertilization event along with the functional specialization of the male gametophyte, are considered to be key innovations in the evolutionary success of flowering plants. This review encompasses important recent advances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
258
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(269 citation statements)
references
References 87 publications
7
258
0
2
Order By: Relevance
“…Thanks to the fast progress in expression profiling and micromanipulation technologies, gene expression is being reported not only for individual structures such as the ovule, the anther, and the male gametophyte, but even at the single cell level such as egg cells and single sperm cells (reviewed in Borg et al, 2009). These approaches are good sound bases for surmounting these difficulties and studying stress response of a specific phase or component of sexual development.…”
Section: Perspectivesmentioning
confidence: 99%
“…Thanks to the fast progress in expression profiling and micromanipulation technologies, gene expression is being reported not only for individual structures such as the ovule, the anther, and the male gametophyte, but even at the single cell level such as egg cells and single sperm cells (reviewed in Borg et al, 2009). These approaches are good sound bases for surmounting these difficulties and studying stress response of a specific phase or component of sexual development.…”
Section: Perspectivesmentioning
confidence: 99%
“…The male germline is segregated in the gametophyte by asymmetric division of the microspore to form the generative (germ) cell, which rapidly establishes a distinct developmental program. This male germ cell then completes a mitotic division and differentiates to form the two sperm cells required for double fertilization (Borg et al, 2009). In contrast, the female germline is only segregated after three rounds of nuclear division followed by cellularization of the embryo sac (Yadegari and Drews, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The generative cell undergoes a symmetric cell division called Pollen Mitosis II (PMII) to produce tricellular pollen, which has a vegetative cell and 2 sperm cells. 1,2 The vegetative cell nucleus and the 2 sperm cells migrate into the pollen tube to the embryo sac for double fertilization. 3 Recent studies have revealed several components and the transcription factors which play important roles during male gametophyte development in Arabidopsis.…”
mentioning
confidence: 99%